Effect of different geographic altitudes on the performance of a conventional solar still with arsenic and boron removal efficiency in an arid zone - Chavez Yavara, Wladimir Antonio (Pontificia Universidad Javeriana, 2018)
Objectives: Report the exploratory study results of the performance of a conventional solar still prototype using seawater and brackish water (river and well) at three locations in northern Chile at different geographical heights. Materials and methods: A solar still with an effective distillation area of 0.54 m2 was used. Three tests were performed with seawater, 1 with river water and 1 with well water.  The temperatures and environmental parameters were measured every 10 minutes for 36 continuous hours. The efficiency was evaluated in terms of seawater and the capacity to remove natural contaminants from brackish water. Results and discussion: The productivity in the three selected areas was 3 and 4 L/m2 for seawater and brackish water, respectively. The removal of boron and arsenic complies with the regulations of the country. Conclusion: The results obtained are of exploratory character for the zones, where the geographic height and the total dissolved solids are factors that determine the performance of a passive solar still, which is higher when water is used with low concentrations of solids.